Gravitational waves and neutrino oscillations in Chern-Simons axion gravity. Issue 1 (1st January 2023) - Lambiase, Gaetano; Mastrototaro, Leonardo; Visinelli, Luca
Abstract: We investigate the modifications in the neutrino flavor oscillations under the influence of a stochastic gravitational wave background (SGWB), in a scenario in which General Relativity is modified by an additional Chern-Simons (CS) term. Assuming that the dark matter halo is in the form of axions, the CS coupling modifies the pattern of the neutrino flavor oscillations at Earth up to a total suppression in some frequency range. At the same time, the SGWB in the halo could stimulate the axion decay into gravitons over a narrow frequency range, leading to a potentially detectable resonance peak in the enhanced SGWB strain. A consistent picture would require these features to potentially show up in neutrino detection from supernovae, gravitational wave detectors, and experiments aimed at the search for axions in the Milky Way halo.